2021
DOI: 10.1186/s40359-021-00522-9
|View full text |Cite
|
Sign up to set email alerts
|

Immigrant and Swedish adolescents’ involvement in organized sports activities: an expectancy-value approach

Abstract: Background Drawing on Eccles’ expectancy-value model, we investigated the associations between parents’ sports-related socialization behaviors in the family context, youth’s sports’ values, and youth’s involvement in organized sports activities in the Nordic countries. More specifically, we tested the mediating effect of youth’s sports’ values on the link between socialization of sports in the family setting and youth’s sports participation. Further, we examined whether any associations were mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 40 publications
(113 reference statements)
0
7
0
Order By: Relevance
“…Many factors may contribute to this. For example, Jaf et al 59 . showed that parental involvement predicted adolescents' dropout 1 year later via sports values.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many factors may contribute to this. For example, Jaf et al 59 . showed that parental involvement predicted adolescents' dropout 1 year later via sports values.…”
Section: Discussionmentioning
confidence: 99%
“…Many factors may contribute to this. For example, Jaf et al 59 showed that parental involvement predicted adolescents' dropout 1 year later via sports values. However, a very concrete factor that organizations and clubs can target is the behavior and motivational style provided by the coach via the motivational climate.…”
Section: Practical Implicationsmentioning
confidence: 99%
“…Participants reported on their age and gender (girls were coded as 0 and boys as 1), and parental employment status, used as a proxy of SES. Further, in line with the practice of scholars (Jaf, Özdemir, & Skoog, 2021;Peguero, 2011;Singh et al, 2008), adolescents with both parents born outside a Nordic country were regarded as immigrants and those with both of their parents born in a Nordic country were regarded as Nordic. A small group of adolescents (7%) had only one parent born outside the Nordic countries.…”
Section: Sociodemographic Characteristics and Covariatesmentioning
confidence: 99%
“…Scholars' research in recent years has also found that the family has a non-negligible influence on the behavior and habits of adults, and the way family upbringing will affect the individual's lifestyle in adulthood ( 2 , 39 , 41 , 42 ). Therefore, in order to ensure the scientific nature of the research, this study believes that discussions such as family annual income and family social class also need to be included in the frame design.…”
Section: Introductionmentioning
confidence: 99%